A modern perspective on the history of semiconductor nitride blue light sources. (September 2015) - Maruska, Herbert Paul; Rhines, Walden Clark
Highlights: This review discusses the history of blue light-emitting diodes since 1923. Particular attention is placed on the slow but steady improvement in device efficiency since the 1970s. Work in the Japanese laboratories where the problems with blue device performance were finally solved in 1996 is emphasized. The discussion concludes with the award of the Nobel Prize in Physics to Nakamura, Akasaki, and Amano in December, 2014. Abstract: In this paper we shall discuss the development of blue light-emitting (LED) and laser diodes (LD), starting early in the 20th century. Various materials systems were investigated, but in the end, the nitrides of aluminum, gallium and indium proved to be the most effective. Single crystal thin films of GaN first emerged in 1968. Blue light-emitting diodes were first reported in 1971. Devices grown in the 1970s were prepared by the halide transport method, and were never efficient enough for commercial products due to contamination. Devices created by metal–organic vapor-phase epitaxy gave far superior performance. Actual true blue LEDs based on direct band-to-band transitions, free of recombination through deep levels, were finally developed in 1994, leading to a breakthrough in LED performance, as well as nitride based laser diodes in 1996. In 2014, the scientists who achieved these critical results were awarded the Nobel Prize in Physics.